Ritual Moibba’: Ritus Peralihan dan Pembentukan Identitas Masyarakat Adat Boano - Maiyo, Midun Sandi Nayon; Aepu, Siti Hajar; Dewi, Citra; Ariyani, Risma; Bakari, Yulianti (CV. Social Politic Genius (SIGn), 2023)
This research aims to understand the processes, symbols, and meanings embedded in the Moibba’ ritual for daughters of the Boano tribe. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the Moibba’ ritual represents a complex rite of passage rich in symbolism, reflecting social transition and identity formation for the Boano tribe’s daughter. This process marks the physical and spiritual transition of the individual undergoing it and communicates the cultural values and spiritual beliefs from the process of womboan (seclusion) until the posugo’an kadera hua’an (sitting on the throne chair). Each specific tool and material, from da’un dauna (betel leaf) to kadera hua’an (throne chair), holds deep symbolic meanings such as protection, cleanliness, honor, and purity, collectively forming a complex tapestry of the Boano tribe’s social and cultural identity. Therefore, it is recommended that the Department of Education and Culture of Parigi Moutong Regency, Customary Institutions, Indigenous Elders, and the Boano indigenous community take strategic steps to preserve and promote the Moibba’ ritual. This includes developing educational programs aimed at enhancing the awareness and understanding of the younger generation about the values and symbolism contained in the Moibba’ ritual, as well as its importance in identity formation and the maintenance of social bonds within the Boano indigenous community. Integrating knowledge about this rite into the local school curriculum is also suggested to ensure the sustainable transmission of cultural knowledge. Developing cultural initiatives such as festivals or exhibitions showcasing the Moibba’ ritual can enhance public appreciation of the Boano tribe’s cultural heritage while strengthening social networks and solidarity among the indigenous people. With these measures, it is hoped that the Moibba’ ritual and the cultural richness of the Boano tribe can be preserved and continue to thrive amidst the challenges of modernity and globalization.